Maps and Geographical Names as Tokens of National Interests: The Spitsbergen vs. Svalbard Case - Arlov, Thor Bjørn (Nordlit, 2020)
The treaty of 9 February 1920 granted Norway full sovereignty over the ‘Archipelago of Spitsbergen’, by which name this Arctic territory was known at the time. Assuming sovereignty five years later, Norway altered the official name to ‘Svalbard’. To what extent was the name-change a token of national interests or even blatant nationalism? This paper outlines the origin and usage of the place-names Spitsbergen and Svalbard in light of the area’s mapping and nomenclature and with an emphasis on national bias. It briefly discusses the different practices and principles of geographical naming. This paper proposes that the change in official nomenclature from Spitsbergen to Svalbard in 1924–1925, though partly due to justifiable practical considerations, was primarily a political act to construct national bonds with the newly won territory. Although perceived as part of a ‘Norwegianization’ process in the northern regions, the name-change itself was not intended to provoke foreign reactions, but rather to satisfy a domestic audience.